Exploratory Study on the Formation of Trigonometric Concepts by High School Students - Dini Wardani Maulida; Setiya Antara; Masduki Masduki (Didaktik Matematika, 2025)
The students formation of mathematical concepts was still relatively weak. Data from the PISA showed that procedural skills still dominate students' conceptual understanding. The purpose of this study was to describe the students' concept formation in solving trigonometric problems. This study used a qualitative approach with a case study design. The subjects were three tenth-grade students from one of the high schools in the Boyolali district, Central Java. The instruments included trigonometric tests and in-depth interviews. Then the data was analyzed through reduction, presentation, and conclusion. The results showed that students with high trigonometric ability can fulfill all indicators of concept formation and connect trigonometric concepts with others. Furthermore, the student with medium trigonometric ability, although he can fulfill all the indicators of concept formation, has errors in the calculation process and unable to connect trigonometric concepts with other mathematical concepts. A student with low trigonometric ability is only able to perform simple solutions, and difficulties in connecting trigonometric concepts with others and explaining the steps of the solution. The implications of this study are the importance of pedagogical intervention in strengthening students' conceptual understanding and providing concrete experiences in trigonometry, especially for students with medium and low abilities.